2021
DOI: 10.1128/spectrum.01364-21
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of a Neodymium-Doped Yttrium Aluminum Garnet 1,064-Nanometer Laser against Sporothrix globosa by Inducing Apoptosis and Pyroptosis via the NLRP3/Caspase-1 Signaling Pathway: In Vitro and In Vivo Study

Abstract: Nd:YAG 1,064-nm laser irradiation is a useful alternative for the treatment of sporotrichosis, especially in patients with liver dysfunction, pregnant women, and children, for whom the administration of antifungal drugs is not suitable. It may improve the overall treatment effect by shortening the duration of antifungal treatment and reducing tissue inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Therefore, the Bax and Bcl-2 protein level changes will aggravate cardiac injury and dysfunction induced by LPS, while relieving these changes might alleviate LPS-induced cardiac damage. Besides, the proteins of cleaved-Casepase-1 and cleaved-Casepase-3 also play a vital part in developing cardiac apoptosis [27]. In the current study, LPS triggered myocardial apoptosis, as evidenced by elevations in cleaved-Casepase-1, cleaved-Casepase-3, Bax protein levels, and decreased Bcl-2 protein level.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, the Bax and Bcl-2 protein level changes will aggravate cardiac injury and dysfunction induced by LPS, while relieving these changes might alleviate LPS-induced cardiac damage. Besides, the proteins of cleaved-Casepase-1 and cleaved-Casepase-3 also play a vital part in developing cardiac apoptosis [27]. In the current study, LPS triggered myocardial apoptosis, as evidenced by elevations in cleaved-Casepase-1, cleaved-Casepase-3, Bax protein levels, and decreased Bcl-2 protein level.…”
Section: Discussionsupporting
confidence: 57%
“…The study by Yan et al, 2021 also demonstrated the laser's effect on S. globosa cells, inducing apoptosis and pyroptosis via NLRP3/Caspase-1, activated by the TH1/TH17 cellular response. This type of treatment aligns with the clinical presentation of the treated feline's ear lesion, as it is believed that laser therapy assisted the immune system in combating the lesion's microorganisms [ 17 ].…”
Section: Discussionmentioning
confidence: 91%
“…PRRs expressed on the surfaces of epithelial cells and dendritic cells can help with the recognition of pathogens. PRRs, including Mannose receptors, Dectin-1, toll-like receptors, and NOD-like receptors, have been reported to be involved in the immune process 34 , 35 . The innate immunity represents the host's first line of defense against pathogens 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the NOD-like receptor protein 3 (NLRP3) inflammasome plays a critical role against S. globosa infection. Yan et al 35 treated the footpads of S. globosa -infected mice with Nd:YAG 1064 nm laser irradiation, and concluded that the local NLRP3/caspase-1 pyroptosis pathway was activated and promoted Th1/Th17 cell immunity, and the critical effector of pyroptosis caspase-3 was upregulated after the laser treatment. Gonçalves et al 52 found that NLRP3, ASC, or caspase-1 knockout mice were more susceptible to S. schenckii infection than wild-type mice, suggesting that NLRP3-triggered-inflammatory responses contributed to host protection against infection.…”
Section: Discussionmentioning
confidence: 99%